ANALISIS KOHESI GRAMATIKAL DAN LEKSIKAL DALAM NOVEL “THE BOOK OF ALMOST” KARYA BRIAN KHRISNA - Anggun Sita Dewi; Atiqa Sabardila (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to (1) describe the analysis of grammatical cohesion in the novel "The Book of Almost" by Brian Khrisna, and (2) describe the analysis of lexical cohesion in the novel "The Book of Almost" by Brian Khrisna. This research is a qualitative descriptive study. The data analysis method used by the author is a qualitative descriptive method with note-taking techniques, content analysis, and content analysis. The implementation of this technique is by listening to the sentences in the Novel "The Book of Almost" by Brian Khrisna which have grammatical cohesion and lexical cohesion markers. Furthermore, the researchers analyzed the data using content analysis techniques by paying attention to grammatical and lexical cohesion aspects. Then the next analysis technique is the content analysis technique. The author analyzes the contents of the novel in the form of a written essay and is reviewed in a literature study. The results showed that in the novel The Book of Almost by Brian Khrisna there were 26 data found. The data consists of 7 reference data, 3 data ellipsis, 9 conjunction data (4 coordinating conjunction data and 5 subordinating conjunction data), 4 antonym data, and 3 synonym data.